A Critical Look on the Student's Internet Use – An Empirical Study - Victoria Stanciu; Andrei Tinca (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The exponential development of the Internet has impacted the socio-economical, political life and individuals' life and will continue to significantly impact the society in all its aspects. Internet has changed the business environment, the socio-political domains and peoples' behavior and cultural values. In this contexts, the authors' survey aimed at identify and understand the Internet users' profile of the students in one of the Romanian faculty. The survey revealed the students' Internet use and time spending on Internet. The research emphasized that the survey's respondents could be considered "extensive" Internet users for personal needs and less effective users for professional purposes. The study's findings provided important insights regarding Internet access and use preferences of our students and emphasized how the teaching process can exploit, in an effective way, the students' skills and appetite for Internet use. The findings pointed out the needed updates in the academic curriculum aiming at providing skills and knowledge in regard with Internet effective use for learning and professional purposes. The research on this area is scarce in Romania, and the authors' research results provide an useful insight on how Internet use can be improved in the academic institutions.
Keywords: A22; A23; M15; 650; Internet; user; Internet learning; information resources; higher education